Small cell lung cancer transformation and tumor heterogeneity after sequential targeted therapy and immunotherapy in EGFR-mutant non-small cell lung cancer: A case report - Yang, Meng-Hang; Yu, Jia; Cai, Chen-Lei; Li, Wei (Frontiers in Oncology, 2022)
Background: Histological transformation from non-small cell lung cancer (NSCLC) to small cell lung cancer (SCLC) is one of mechanisms of the acquired resistance to epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKI). However, SCLC transformation and tumor heterogeneity have never been reported in sequential targeted therapy and immunotherapy. Case presentation: Here, we described a patient with advanced EGFR-mutant NSCLC, who received erlotinib and underwent the resistance with EGFR T790M (-). The patient then received chemotherapy plus immunotherapy of programmed cell death 1 (PD-1) inhibitor, encountered progression with pathological transformation from NSCLC to SCLC that was overcome by chemotherapy of etoposide plus carboplatin (EC) with the main lesion significantly shrinking while metastatic nodules increasing. The pathology of the metastatic nodule showed NSCLC with EGFR T790M (+). Based on the tumor heterogeneity, EC chemotherapy combined with osimertinib was used, and patients responded well. The patient experienced four lung biopsies in all, which helped to provide the patient with precise treatment. Conclusions: This case suggested that SCLC transformation and tumor heterogeneity should be paid attention to when disease progression occurred in advanced NSCLC whether receiving targeted therapy or immunotherapy.